Anterior cruciate ligament reconstruction using peroneus longus tendon auto-graft: functional results - Khamis, Ahmed Refaat; Aziz, Mohamed Tarek Abdel; El Sayed, Magdy Mohamed; Baky, Mohamed Ahmed Abdel (International Journal of Research in Orthopaedics, 2024)
Background: The peroneus longus tendon is a promising autograft alternative to the others tendons in ACL reconstruction. It offers the advantages of being expendable, having adequate length and strength, sparing morbidity from other donor sites, and allows early rehabilitation. Methods: The study was on 30 patients with isolated ACL complete tear treated by arthroscopic reconstruction using the PL tendon in Benha university hospital in the period from July 2022 till June 2023. The patients were assessed pre-operatively and post-operatively with the IKDC score and clinical tests of instability. The ankle was also assessed pre-operatively and post-operatively though AOFAS and clinical tests of instability. Patients were followed up for 12 months. Results: The age of patients was 18-45 years. The preoperative IKDC score ranged 49-72 with a mean SD of±14.02. The post-operative IKDC score ranged 89-100 with a mean SD of±3.5 showing marked improvement of knee function with 93.3% of patients regained normal knee function. The pre-operative AOFAS score ranged 99-100 with a mean SD of±0.16 and the post-operative score ranged 89-100 with a mean SD of±3.5 denoting minimal affection of ankle functions. Conclusions: The peroneus longus serves as a suitable autograft for ACL reconstruction as an alternative to the others tendons based on its ability to restore knee function and the minimal morbidity at the donor site.